The evaluation of a multiplex PCR-DNA dipstick assay with culture method and EZ Typhi Carrier DNA assay to detect Salmonella Typhi in well water samples - Nor A.Z.; Salwani H.; Norain Haslinie H.; Mohd Nuramin A.; Norhafiza N.; Haslizai H.; Asma I.; Aziah I. (Elsevier B.V., 2024)
Indexed by Scopus